Experimental behaviour of FRP reinforced concrete structural elements. (2022) - Loganathan, P.; Shyamala, G.; Ramesh, S.
Abstract: Reinforced concrete structures form a major part of the Engineering infrastructures of all developed countries and their integrity over long periods of service is of vital economic importance. However, there are a number of factors that can endanger the serviceability of reinforced concrete structures. These factors result in high maintenance costs (or) the early replacement of structures. The most widespread problem of premature deterioration is caused by deterioration of steel reinforcement. Corrosion induced deterioration of steel reinforcement in concrete has increasingly become a major problem use of non-metallic reinforcement such as GFRP (Glass Fibre Reinforced Polymer) rebars helps to rise the mechanical characteristics of concrete structure as it does not corrode. The GFRP rebars look like steel with similar, properties such as high tensile strength and bond characteristics. The key aim of this project is to replace the steel reinforcement by using GFRP rebars in concrete structural elements and to find the load carrying capacity etc., and comparing with the test results of the experiment carried out on the same size of beams with use of GFRP and tor steel as reinforcement. Reinforcement rod 8 mm size 3 at bottom and 2 at top is placed with stirrup spacing of 100 mm c/c. Load applied in 3 Kn variation and 7 cycles of load was applied. Load carrying capacity was good at 0.1 % GFRP addition.